Numerals ending in -kroć in the Electronic Dictionary of the 17th- and 18th-century Polish - Wieczorek, Aleksandra (Papers in Linguistics, 2025)
The article presents grammatical characteristics and description of the functioning of numerals ending in -kroć in Polish texts from the 17th and 18th centuries. The analysis concerns lexemes from DWAKROĆ [‘two times’] to DZIEWIĘĆKROĆ [‘nine times’] excerpted from the material found in the Electronic Corpus of 17th- and 18th-century Polish Texts. The research results were used to create lexical entries for the analysed words in the Electronic Dictionary of the 17th- and 18th-century Polish.